Analisis Pembiayaan Kesehatan Bersumber Pemerintah di Kota Serang Tahun 2014 – 2016 - Estherlina Sitorus; Atik Nurwahyuni (Jurnal Kebijakan Kesehatan Indonesia, 2017)
ABSTRACTBackground:This study aims to obtain information about health financing based on sources and utilization of funds derived from the government in Serang City year 2014-2016, as well as commitment from the local government of Serang City towards health financing by using approach District Health Account (DHA. The results showed that the total budget for health financing funded by the government in Serang City from 2014-2016 has increased in 2014 amounting to Rp 61,759,128,963, in year 2015 it was amounting to Rp 77,302,110,763 and in year 2016 of Rp 88,278,652,111. The proportion of APBD Serang City in the Year 2014 was 6.02%, Year 2015 was 6.99% and Year 2016 was 7.79%. This shows the commitment of Serang City government to funding the health sector. From the perspective of Health financing by function, the largest percentage is health system governance functions and for curative services. From the perspective of the program, many is allocated for health system strengthening program 59,55% -67,43%. While from the perspective of budget, most is allocated for the operational expense (83.68% -93.57%). With limited resources while increasing health needs, it will require the efficient use of existing resources as well as the selection of effective health program activities, and the need to make health budgeting policy as the basis or reference of health budget planning in Serang City. Keywords: Health Financing, DHA, Health Expenditure ABSTRAKPenelitian ini bertujuan untuk memperoleh informasi tentang pembiayaan kesehatan berdasarkan sumber dan pemanfaatan dana yang berasal dari pemerintah di Kota Serang Tahun 2014- 2016, serta komitmen dari pemerintah Daerah Kota Serang terhadap pembiayaan kesehatannya dengan menggunakan pendekatan District Health Account (DHA). Hasil penelitian menunjukan bahwa total anggaran untuk pembiayaan kesehatan bersumber pemerintah di Kota Serang dari Tahun 2014-2016 mengalami peningkatan yaitu pada Tahun 2014 sebesar Rp 61.759.128.963, Tahun 2015 sebesar Rp 77.302.110.763dan Tahun 2016 sebesar Rp 88.278.652.111. Jika dilihat dari persentase APBD Kota Serang pada Tahun 2014 sebesar 6,02%, Tahun 2015 sebesar 6,99% dan Tahun 2016 sebesar 7,79%. Hal ini menunjukan komitmen pemerintah Kota Serang terhadap pendanaan sektor kesehatannya. Pembiayaan kesehatan berdasarkan fungsi, persentase terbesar untuk fungsi tata kelola sistem kesehatan dan untuk pelayanankuratif. Berdasarkan program, banyak terealisasi untuk program penguatan Sistem kesehatan 59,55%-67,43%, berdasarkan mata anggaran, paling besar untuk belanja operasional (83,68%- 93,57%). Dengan sumber daya yang terbatas sedangkan kebutuhan kesehatan yang terus meningkat, maka diperlukan efisensi penggunaan sumber daya yang ada serta pemilihan program kegiatan kesehatan yang efektif, serta perlunya dibuat kebijakan penganggaran kesehatan sebagai dasar atau acuan perencanaan anggaran kesehatan di Kota Serang. Kata Kunci: Pembiayaan Kesehatan, DHA, Belanja Kesehatan